x*3-6=x*12-177

Simple and best practice solution for x*3-6=x*12-177 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*3-6=x*12-177 equation:


Simplifying
x * 3 + -6 = x * 12 + -177

Reorder the terms for easier multiplication:
3x + -6 = x * 12 + -177

Reorder the terms:
-6 + 3x = x * 12 + -177

Reorder the terms for easier multiplication:
-6 + 3x = 12x + -177

Reorder the terms:
-6 + 3x = -177 + 12x

Solving
-6 + 3x = -177 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-6 + 3x + -12x = -177 + 12x + -12x

Combine like terms: 3x + -12x = -9x
-6 + -9x = -177 + 12x + -12x

Combine like terms: 12x + -12x = 0
-6 + -9x = -177 + 0
-6 + -9x = -177

Add '6' to each side of the equation.
-6 + 6 + -9x = -177 + 6

Combine like terms: -6 + 6 = 0
0 + -9x = -177 + 6
-9x = -177 + 6

Combine like terms: -177 + 6 = -171
-9x = -171

Divide each side by '-9'.
x = 19

Simplifying
x = 19

See similar equations:

| 27y^7+24y^4=0 | | x^2-x=462 | | 4x^2-6x-10=00 | | 3c+9=6(1c+9) | | 2x+37=4x-9 | | n=-120 | | 0.66+2y=4y-0.13 | | -6x-10=2+14 | | 5(12+4)=8x | | 490=-7n | | x^2+34x+11=0 | | 3x+24=38 | | 42=14n | | X+4y=1 | | 157-2x=34x+23 | | -21.536=1.6(9-m) | | x+x+1+x+4=-18 | | x*.5+2=0.33 | | 18x=180 | | x^3-2x^2-47x-6=0 | | 17-x=28-2x | | -0.1667(x-18)+0.5(x+2)=x-20 | | 4x^2+70x-304=0 | | 5x^2+7x+5x=0 | | 5x-15=8x-36 | | 25xy^2-36x=0 | | 8(3g-2)=4(7g-1) | | 2x+33=3+8x-6 | | 8a^2-2ab-b^2=0 | | x^2-2.3x+5.1=0 | | 4.85+.65r=6.80 | | 4+3a-6=3a+2-a |

Equations solver categories